1998
DOI: 10.1021/ac9712456
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Impedance Spectroscopy of Platinum Ultramicroelectrodes in Flowing Solutions

Abstract: A method for studying impedance spectroscopy of micrometer-sized electrodes in the frequency range from 5 kHz to 5 MHz has been developed and tested. Details of the electronic circuit and the data processing method are provided. Since the method involves high-speed data acquisition and fast Fourier transformation, the impedance data can be obtained within a 5-ms time window. This enables measurement of changes in the electrode impedance caused by rapid changes in the solution composition. In particular, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 25 publications
2
36
0
Order By: Relevance
“…14 In Fig. 2, a diagram of the applied potential waveform during cyclic voltammetric measurements is shown.…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
“…14 In Fig. 2, a diagram of the applied potential waveform during cyclic voltammetric measurements is shown.…”
Section: Data Acquisition and Processingmentioning
confidence: 99%
“…The counter electrode was a Pt wire (surface area about 0.5 mm 2 ) and a saturated KCl calomel electrode (SCE, miniature model; Fisher Scientific, Ottawa, Canada) was used as reference electrode. The working electrode consisted of an Hg-film (6 mm thick)/Au mm-electrode, which was prepared by computer-controlled electrodeposition of a layer of Hg onto a 25 mm Au disk electrode under constant current conditions in a 0.1 mol/L Hg 2 (ClO 4 ) 2 and 1 mol/L HCl 4 solution [18]. The Hg-film electrode was washed with water and operating buffer solution, and then aligned to the capillary outlet at a distance of 30 mm with a micropositioner.…”
Section: Apparatus and Proceduresmentioning
confidence: 99%
“…Some chronoamperometric experiments have been done in SECM, [19][20][21][22] but only a few studies have been reported on SECM in ac mode. [23][24][25][26][27][28][29][30] Schuhmann et al developed an ac-SECM mode for mapping domains of different conductivity or electrochemical reactivity on surfaces. [31][32][33][34] Their approach is different from that presented here, because they applied a frequency perturbation to the probe, whereas in this work the perturbation is applied to the substrate.…”
Section: Introductionmentioning
confidence: 99%